CERITA LISAN “YONG DOLLAH”: PEWARISAN DAN RESISTENSI BUDAYA ORANG MELAYU BENGKALIS - Marhalim Zain (Balai Bahasa Provinsi Riau, 2014)
Humorous stories Yong Dollah is one form of oral literature that very popular in Bengkalis Malay community. Yong Dollah is a nickname of a Malay's character. His real name is Abdullah bin Endong, who is expected to be born in Bengkalis around 1906. One of the inheritance strategy of Yong Dollah oral stories which makes distribution spreaded widely and became popular by telling the story about him in front of friends at the coffee shop, in spare time. Activities